Lipocalin-2 in neutrophils induces ferroptosis in septic cardiac dysfunction via increasing labile iron pool of cardiomyocytes - Huang, Yuxue; Zhang, Ning; Xie, Cuiping; You, Yayu; Guo, Lei; Ye, Feiming; Xie, Xiaojie; Wang, Jian’an (Frontiers in Cardiovascular Medicine, 2022)
Cardiac dysfunction is a frequently compliance of sepsis with high mortality. The present study was designed to identify the effect of neutrophils-derived Lipocalin-2 (LCN2) in septic cardiac dysfunction (SCD) and its potential mechanism. Wild type (WT) and LCN2 knockout (LCN2 KO) mice were peritoneally injected with lipopolysaccharide (LPS) to induce SCD. Cardiac function was assessed 12 hours after LPS injection by echocardiography. Cardiac tissue was harvested for the evaluation of malonaldehyde (MDA), prostaglandin E synthase 2(PTGS2) mRNA level. LPS induced ferroptosis and SCD in mice. LCN2 deficiency attenuated cardiac injury post LPS administration. In vitro, LCN2 expression in neutrophils increased in response to LPS. Ferroptosis of cardiomyocytes induced by conditioned medium (CM) from LPS-induced neutrophils of WT mice could be attenuated in conditioned medium (CM) from LPS-induced neutrophils of LCN2 KO mice. Exogenous LCN2 induced H9C2 cells ferroptosis via increasing labile iron pool (LIP). In conclusion, our results showed that LCN2 deficiency prevented heart dysfunction and ferroptosis in SCD mice and suggested that neutrophil-derived LCN2 might be a promising therapeutic target for SCD.